2019
DOI: 10.1007/s10068-019-00560-5
|View full text |Cite
|
Sign up to set email alerts
|

The fermentation characteristics of soy yogurt with different content of d-allulose and sucrose fermented by lactic acid bacteria from Kimchi

Abstract: In this study, to understand whether D-allulose, an ultra-low calorie sweetener, was available in soy yogurt fermentation, we isolated Leuconostoc mesenteroides and Lactobacillus plantarum from kimchi and fermented in soymilk at various contents of D-allulose and sucrose. The lactic acid bacteria counts in soy yogurt had the highest range of 9.23-9.49 log CFU/g at 24 h fermentation and then decreased. At 48 h fermentation, the pH showed 4.31 and 4.52 in the samples containing 75% and 100% D-allulose as sweeten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 22 publications
1
7
0
3
Order By: Relevance
“…This phenomenon also might be due to the ability of LAB to grow in plant-based milk alternatives. The growth of LAB has been identified in plant-based yogurt alternatives such as in soymilk, lupin based, and cereal-based yogurt alternatives ( Coda et al, 2011 ; Hickisch et al, 2016 ; İçier et al, 2015 ; Kim & Han, 2019 ; Rasika et al, 2021 ). In general, this study had a shorter incubation period than that in previous reports, which might be depending on the incubation temperature, inoculum types, and ingredients used.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon also might be due to the ability of LAB to grow in plant-based milk alternatives. The growth of LAB has been identified in plant-based yogurt alternatives such as in soymilk, lupin based, and cereal-based yogurt alternatives ( Coda et al, 2011 ; Hickisch et al, 2016 ; İçier et al, 2015 ; Kim & Han, 2019 ; Rasika et al, 2021 ). In general, this study had a shorter incubation period than that in previous reports, which might be depending on the incubation temperature, inoculum types, and ingredients used.…”
Section: Resultsmentioning
confidence: 99%
“…The pH and lactic acid concentrations range around 5.1-5.4 and 3.0-5.7 mg•mL −1 , respectively. Kim et al [38] introduced soy yogurt fermented by Leuconostoc mesenteroides and L. plantarum from kimchi, wherein the pH and titratable acidity after 24 h were around 4.5% and 0.8%. Moreover, Liu et al [34] demonstrated the acidification rate of S. thermophilus ATCC BAA-250 during soy milk fermentation.…”
Section: Discussionmentioning
confidence: 99%
“…Proses fermentasi pada sari kedelai diketahui dapat meningkatkan penyerapan isoflavon, asam amino, dan aktivitas antioksidan, serta dapat menekan rasa khas kedelai sehingga meningkatkan karakteristik sensori [2]. Soyghurt dan yoghurt dibuat dengan proses fermentasi menggunakan bakteri asam laktat dan memiliki tekstur semi solid serta berasa asam.…”
Section: Pendahuluanunclassified
“…Nilai pH produk yoghurt dan soyghurt pada penelitian ini dapat dilihat pada Tabel 1. Nilai pH pada produk susu dan sari kedelai cenderung mendekati pH netral yaitu dengan nilai 6.5 dan 6.8 dan terus menurun selama proses fermentasi [2], [7]. Nilai pH pada produk yoghurt dan soyghurt diketahui mengalami penurunan menjadi 4 pada yoghurt starter komersial dan 5 pada yoghurt back slope, soyghurt back slope dan soyghurt starter komersial.…”
Section: Nilai Ph Produk Yoghurt Dan Soyghurtunclassified